2019
DOI: 10.1111/petr.13573
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of rabbit anti‐thymocyte globulin vs basiliximab induction in pediatric liver transplant recipients

Abstract: Literature is limited comparing induction immunosuppression in pediatric liver transplant (LTx) recipients. This is a single‐center, retrospective cohort study of primary pediatric liver transplants at our center between 2005 and 2016 who received either basiliximab (BSX) or rabbit anti‐thymocyte globulin (rATG) induction. Maintenance immunosuppression consisted of tacrolimus ± a corticosteroid taper. Exclusions included receipt of an ABO‐incompatible graft, retransplantation, and multi‐organ transplantation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(26 reference statements)
0
4
1
Order By: Relevance
“…In cost-effective analysis, they found the use of ATG induction resulted in a substantial reduction in drug costs compared to basiliximab. 16 While Newland et al 11 compared ATG to basiliximab induction in children, the primary endpoint was not changes in renal function post liver transplant, and unlike our study, they demonstrated an increase of both rejection and infection when comparing ATG to basiliximab in their cohort.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In cost-effective analysis, they found the use of ATG induction resulted in a substantial reduction in drug costs compared to basiliximab. 16 While Newland et al 11 compared ATG to basiliximab induction in children, the primary endpoint was not changes in renal function post liver transplant, and unlike our study, they demonstrated an increase of both rejection and infection when comparing ATG to basiliximab in their cohort.…”
Section: Discussioncontrasting
confidence: 66%
“…10 Pediatric studies on ATG induction for the purpose of preventing CNI-induced renal dysfunction are limited. Newland et al 11 reviewed the use of ATG vs basiliximab induction in a single center fashion. While effects of induction on post-transplant renal function were not evaluated in this study, the ATG group had a paradoxical increase in biopsy proven acute cellular rejection compared to basxiliximab.…”
Section: Introductionmentioning
confidence: 99%
“…Induction protocols ranged from none to pulse steroids alone to pulse steroids with antibody induction therapy. Limited data exist comparing these strategies head to head, although some studies have suggested increased rejection with the addition of anti‐thymocyte globulin 5,20 . Only four of the responding centers used anti‐A or anti‐B antibody titers to guide therapy in ABO‐incompatible grafts.…”
Section: Discussionmentioning
confidence: 99%
“… 7 If this drug is not tolerated, another purine antimetabolite, azathioprine, or a mammalian target of rapamycin (mTOR) inhibitor, rapamycin, can be added to tacrolimus and steroids. Some regimens also include interleukin-2 (IL-2) receptor-blocking or lymphocyte-depleting antibodies from the time of LT. 8 , 9 Time-dependent protocols are used to reduce tacrolimus and steroid doses, based on the likelihood of rejection at various times after Tx. Such reductions can precipitate rejection in some individuals.…”
Section: Introductionmentioning
confidence: 99%